THE IMPACT OF PAKISTAN’S REFUGEE POLICY ON INTERNATIONAL RELATIONS: A CASE STUDY OF AFGHAN REFUGEES - Rana Rahman; Roheen Zafar; Fazli Rahman (Journal of Religion and Society, 2025)
Pakistan’s refugee policy, particularly in relation to Afghan refugees, has had profound implications for its international relations, regional security, and domestic socio-economic landscape. Since the Soviet invasion of Afghanistan in 1979, Pakistan has hosted millions of Afghan refugees, making it one of the largest refugee-hosting countries in the world. This paper examines the evolution of Pakistan’s refugee policy, focusing on the challenges and opportunities it presents in the context of international relations. The study highlights the humanitarian, economic, and security dimensions of hosting Afghan refugees, emphasizing the strain on Pakistan’s resources and infrastructure, as well as the cultural and social integration challenges faced by both refugees and host communities. The paper also explores the geopolitical implications of Pakistan’s refugee policy, particularly its impact on diplomatic relations with Afghanistan and other regional and global stakeholders. It analyzes the role of international organizations, such as the UNHCR, in providing humanitarian assistance and the limitations of such aid in addressing the long-term needs of refugees. Furthermore, the study discusses the security concerns associated with hosting Afghan refugees, including the potential for instability and terrorism, which have influenced Pakistan’s policy decisions. By comparing Pakistan’s refugee policies with those of other countries, the paper identifies best practices and offers recommendations for improving refugee management in line with international norms. The findings suggest that while Pakistan’s refugee policy has been shaped by a mix of humanitarian obligations and national interests, a more sustainable and comprehensive approach is needed to address the protracted refugee crisis and its broader implications for regional and global security. Keywords: Pakistan, Afghan Refugees, Refugee Policy, International Relations, Humanitarian Assistance, Security Implications, Regional Dynamics, UNHCR, Socio-Economic Impact.